Pengembangan Buku Ilmiah Populer Keanekaragaman Mangrove Berbasis Pembelajaran Kontekstual Pada Materi Keanekaragaman Hayati di SMA: The Development of Popular Scientific Book Mangrove Diversity Base on Contextual Learning Material of Biodiversity in Senior High School - Pipit Ummy Utami; Upik Yelianti; Winda Dwi Kartika (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
The school and the surrounding environment are learning resources for students, including the mangrove ecosystem. The innovation of utilizing contextual-based learning resources regarding mangroves has the potential to be used as material for making learning media such as popular science books. This study uses the ADDIE model (analysis, design, development, implementation, and evaluation). The test subjects consisted of two biology teachers, eight class X students of SMAN 1 Kuala Tungkal, and two teachers of biology at SMAN 1 Jambi City. The data collection instrument is a questionnaire. The data obtained is in the form of quantitative and qualitative data. The validation results by material experts obtained 78.7% (good category), and the validation results by media experts obtained 91% (very good category). Trials by teachers obtained 84.58% (very good category), and small group trials received a percentage of 81.76% (very good category). Based on the study results, it can be concluded that the learning media for popular scientific books on mangrove diversity is suitable for use in the learning process both at school and in independent learning. This media can be used as an alternative learning media on biodiversity material.